4P Relationship (Product, Price, Place, Promotion) in Purchasing Decisions for Virtual Reality (VR) as a Learning Medium for Nursing Students - Audly, Tazkia Badliana; Susanti, Raini Diah; Hermayanti, Yanti (Journal of Nursing Care, 2023)
IIntroduction: VNursLab Plus Universitas Padjadjaran offers technology-based learning media, namely virtual reality (VR) to support the clinical skills of nursing students. Before mass marketing, VNursLab Plus products need to be researched in several segmentations. Marketing mix 4P (Product, Price, Place, and Promotion) is one of the marketing strategies carried out to influence the purchasing decision of a product. The purpose of this study was to analyze the relationship between 4P (Product, Price, Place, and Promotion) on VR purchasing decisions in college students. Research methodology: correlational research with a cross sectional approach and the respondents of this study were 89 Universitas Padjadjaran Nursing students who had tried using VR. The instrument used is an adaptation of previous research instruments that the researcher modified. Result: The Chi-Square test obtained a p value <0.01 in each variable product, price, and place on purchasing decision decisions, while the promotion variable on purchasing decisions produced a p value = 0.29. Discussion: The test results state that there is a relationship that makes the 4P marketing mix strategy (Product, Price, Place, Promotion) on VR purchase decisions, so that it can be adapted by VNursLab Plus by considering products, prices, places, promotions as marketing strategies before being marketed to broad segments. Conclusion: There is a relationship between the 4Ps (Product, Price, Place, Promotion) on VR purchase decisions in students as an additional learning method. So that VR can also be applied to streamline student learning.